2010
DOI: 10.1248/bpb.33.260
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Kolaviron, a Biflavonoid from Garcinia kola Seeds, in Brain of Wistar Albino Rats Exposed to Gamma-Radiation

Abstract: This study was designed to evaluate the protective effect of kolaviron (KV), a biflavonoid from Garcinia kola seeds, against g g-radiation (5 Gy)-induced oxidative stress in brain of Wistar rats. Vitamin C (VC) served as standard antioxidant. Forty-four rats were divided into 4 groups of 11 animals each. One group was un-irradiated (normal), two groups were treated with KV and VC (250 mg/kg) for 6 weeks prior to and 8 weeks after irradiation, and fourth group was only irradiated. Rats were sacrificed 1 and 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…1 Also kolaviron has been shown to protect neurons against gamma radiation induced oxidative stress. 20 The present study indicates that kolaviron at various doses, does not cause neurodegenerative changes in the hippocampus and striatum.…”
Section: Discussionsupporting
confidence: 56%
“…1 Also kolaviron has been shown to protect neurons against gamma radiation induced oxidative stress. 20 The present study indicates that kolaviron at various doses, does not cause neurodegenerative changes in the hippocampus and striatum.…”
Section: Discussionsupporting
confidence: 56%
“…Due to the antioxidant properties of kolaviron, it has the potential to protect the neurons of the brain from toxic damage. A recent study has shown kolaviron to protect the neurons against gamma radiation induced oxidative stress in brain of exposed rats [13].…”
Section: Introductionmentioning
confidence: 99%
“…of the whole-body irradiated rats, indicating the presence of radiation-induced oxidative damage. Moreover, the study of Adaramoye (2010) showed an increase of serum levels of MDA, urea and activities of ALT, AST and decrease of GSH level and activities of GST, CAT and SOD in rats exposed to 5 Gy γ-radiation. The observed increased level of MDA may be due to the attack of free radicals on the fatty acid component of membrane lipids (Kamat et al, 2000), leading to lipid peroxidation.…”
Section: Discussionmentioning
confidence: 96%